Does tax enforcement counteract the negative effects of terrorism? A case study of the Basque country - Luca Salvadori (European Regional Science Association (ERSA), 2015)
This paper analyses the impact of terrorism on tax enforcement policies by focusing on the case of the Basque Country. The presence of externalities in tax administration attributable to the costs of terrorism is investigated by undertaking a theoretical analysis. The findings of this are tested using Spanish data extracted from repeated surveys and other sources. By employing ordered response models, evidence is found of the negative impact of terrorism on tax enforcement as it is perceived by residents in the Basque Country and Navarre. In particular, this impact is found to be stronger for entrepreneurs and liberal professionals. No significant impact is found for individuals resident in the rest of Spain. MAIN RESULT: This study provides evidence of the fact that the tax administrations of the Basque Country and Navarre employ tax enforcement as an instrument to counter the negative impact that terrorist activity has on tax bases, tax revenues and, in short, on the economy as a whole. This result suggests that previous estimations of the impact of terrorism on the Basque economy are implicitly calculated net of the impact of terrorism on tax administration and, thus, they could be considered as lower bound approximations of the actual net effect of this shock on the Basque economic outcomes.
Keywords: H83; H23; D74; 330; tax administration and auditing; fiscal externalities; terrorism